PENGARUH BAURAN PEMASARAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MEUBEL DI UD. SEKAWAN RIMBA WANGKAL GADING KABUPATEN PROBOLINGGO - Muhammad Syarif Hidayatullah (STKIP PGRI Tulungagung, 2016)
Abstract: The present study was conducted to respond to the significant effect between the mixed marketing and quality of the products simultaneously in making decision for buying the products in UD. Sekawan Rimba Wangkal 1 Gading, Probolinggo. The sample of this study is 30 people as the respondent which took the population of UD. Sekawan Rimba Wangkal 1 Gading, Probolinggo. The analysis method used in collecting data is quantitative analysis which doubles linier regression. The result of this study shows that result of F (simultaneous regression) analysis test, show that mixed marketing and the quality of products have the same significant effects in making decision for buying the products in UD. Sekawan Rimba Wangkal 1 Gading, Probolinggo. Based on statistic result of F (simultaneous regression) test, shows that the highest score 14.253 which 0,000 significant scores. It shows that, if the significant scores (p value) ≤ 0,05, then Ha is received and Ho is rejected. The mixed marketing and the quality of products have the same significant effect in making decision for buying the products (furniture’s) in UD. Sekawan Rimba Wangkal Gading Kabupaten Probolinggo, partially. Based on the result of t partial test of mixed marketing has a significant effect in making decision. The result shows 0,374 of coefficient score are significant with 0,034. Meanwhile, the effect of the quality of products in making decision shows 0,262 coefficients score with 0,009. If the significant score (p value) ≤ 0,05, then Ha is received and Ho is rejected. Key words: mixed marketing, quality of the products, making decision (buying)